PENDEKATAN THE QUR’ANIC MILIEU DALAM STUDI AL-QUR’AN (Telaah Pemikiran Angelika Neuwirth dalam The Qur’an in Context: Historical and Literary Investigations into the Qur’anic Milieu) - Ihwan Agustono (Universitas Muhammadiyah Surabaya, 2022)
The study of the Qurâ€™an among Western thinkers seems not monolithic. In the real of orientalists who use historical analysis to respond Islam with a negative value, such as regarding the Qurâ€™an none more than an epigonal text and not much left to be known about the Qurâ€™an. Meanwhile, a positive understanding toward Qurâ€™an has done by some of them, such as Angelika Neuwirth. The differences are more based on Angelikaâ€™s attempt to convey a truly contextual reading of the Qurâ€™an, not contenting its self with dissolving the Qurâ€™an into its Christian, Jewish, and other â€œsourcesâ€, but to allow for the possibility that the Qurâ€™an may turn out to be a text of its own.